Effects of lecithin and lysolecithin additions on growth performance and nutrient digestibility in weanling pigs - Jones, D.B.; Nelssen, Jim L.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred seventy pigs (21 d of age and 12.8 lb initial wt) were used to determine if adding emulsifiers (lecithin and lysolecithin) to starter pig diets affects growth performance and digestibility of nutrients. Treatments were: 1) corn-soy control; 2) diet 1 with soybean oil; 3) diet 1 with tallow; 4, 5, and 6) diet 3 with lecithin replacing 5%, 10%, and 30% of the tallow; 7, 8, and 9) diet 3 with lysolecithin replacing 5%, 10%, and 30% of the tallow. Average daily gain (ADG), average daily feed intake (ADFI), and feed/gain ratio (F/G) were determined weekly during the 35-d experiment. Apparent digestibilities of total fat, unsaturated and saturated fatty acids, nitrogen, and gross energy were determined from fecal samples collected on d 14. The digestibilities of total fat, unsaturated fatty acids and saturated fatty acids were greater for soybean oil than for tallow. The addition of lecithin to tallow improved digestibility, especially the digestibility of saturated fatty acids. The addition of lysolecithin did not improve the digestibility of tallow. At d 14, ADG and ADFI were not affected by treatment. From d 14 to 35, control pigs had poorer F/G than pigs fed the different fat sources. Average daily gain and ADFI were increased when lecithin and lysolecithin were added to the tallow diet. For the entire experiment, ADG was not affected by treatment, although there was a tendency for improved ADG when the emulsifiers were added to the tallow. Feed intake was greater and F/G poorer for control pigs than pigs fed the fat sources. Our results indicate that the addition of lecithin increased the digestibility of tallow, and ADG and ADFI were improved the last 3 wk of the 5-wk experiment when emulsifiers were added to tallow.
Keywords: Swine; Lecithin; Lysolecithin; Growth performance; Nutrient digestibility; Nursery pigs